PENGARUH KOMBINASI TEPUNG TERIGU DENGAN TEPUNG KACANG MERAH (Phaseolus vulgaris L.) TERHADAP KARAKTERISTIK KIMIA, SENSORI KUE PUKIS - Shaka Sakti Prasetyo; Eman Darmawan; Masrukan; Dyah Titin Laswati (Universitas Widya Mataram, 2026)
This study investigated the effect of combining wheat flour and red bean flour on the chemical and sensory characteristics of pukis cake, aiming to identify the optimal concentration of red bean flour. A Randomized Complete Block Design (RCBD) with one factor and six treatment levels was applied. Sensory attributes evaluated included taste, aroma, color, texture, and overall acceptance, while chemical analyses measured moisture content, total dietary fiber, and anthocyanin levels. Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results showed that red bean flour significantly influenced both chemical and sensory properties. Dietary fiber increased from 2.35% to 6.83%, and anthocyanin content rose from 2.06 mg/100g to 14.09 mg/100g. Moisture content showed no significant difference among treatments. Sensory qualities such as aroma, color, texture, and overall acceptance improved with higher concentrations of red bean flour, while taste remained favorable. Treatment P4 produced the best overall results, indicating it as the most optimal formulation. These findings demonstrate the potential of red bean flour as a functional ingredient in enhancing the nutritional and sensory value of traditional bakery products like pukis cake.